Efficacy and day 7 plasma piperaquine concentrations in African children treated for uncomplicated malaria with dihydroartemisinin-piperaquine - Zongo, I; Somé, F; Somda, SA; Parikh, S; Rouamba, N; Rosenthal, P; Tarning, J; Lindegardh, N; Nosten, F; Ouédraogo, J (Public Library of Science, 2014)
Background One promising new Artemisinin-based combination therapies (ACTs) is dihydroartemisinin-piperaquine (DHA-PQ). However, the pharmacokinetics of piperaquine and the relationship between drug levels and clinical efficacy are incompletely characterized, particularly in children. Methods We performed a single-arm open-label trial in Bobo-Dioulasso, Burkina Faso. A total of 379 participants aged 6 months or more with uncomplicated falciparum malaria were enrolled. Each participant received daily dose of DHA-PQ for three days and followed for 42 days. Parasitological efficacy was analyzed, considering rates of recrudescence and overall recurrence. PK was an exploratory endpoint and a priori, no sample size had been determined. Day 7 capillary and venous plasma concentrations of piperaquine were measured in children aged 2–10 years. Results Of the 379 participants, 365 (96.3%) completed 42 days of follow-up. The median daily dose of PQ was 18.5 mg/kg [6.5–24]. Treatment with DHA-PQ was well tolerated with fever and parasitemia resolution within 48 hours in nearly all children. Recurrent malaria within 42 days of follow-up occurred in 31.3% (10/34) of children less than 2 years old, 16.0% (16/106) of those aged 2–5 years, 9.4% (15/160) of those aged 5–10 years, and none (0/68) of those over 10 years old. After genotyping, 3 of 41 recurrent episodes were recrudescence. An exploratory analysis shows that children with successful treatment outcomes had significantly higher median plasma concentrations of PQ compared to those with recurrent malaria within 42 days after therapy, considering either capillary samples (68 ng/ml [50–85] compared to 48 ng/ml [36–55], p<0.001) or venous samples (42 ng/ml [29–59] compared to 25 ng/ml [19–44], p<0.001). Conclusion DHA-PQ was effective for uncomplicated P. falciparum malaria treatment and offers an alternative to other ACTs. Recurrent malaria was mainly due to new infections after treatment and was correlated with low day 7 PQ concentration in the youngest patients.